Four surprises of electronic music - Puckette, Miller (Lumina, 2017)
The evolution of electronic music practice over the past half century has not gone precisely as we expected. In this paper, we describe four respects in which the development of electronic music was either overtaken by unexpected developments, or, itself, headed in new and unexpected directions.